Distributed Online Course for Educator Training - V. A. Starodubtsev; I. V. Ryashentsev (Высшее образование в России, 2020)
The general digitalization of contemporary society leads to a change in the use of learning technology in engineering education. The aim of this article is to present the advantages of the corporate online course for faculty members’ advanced training developed at Tomsk Polytechnic University. The general goal of this course is to supply engineering teachers with the new tools for their professional activities. Based on the analysis the different types of Massive Open Online Courses (MOOCs), the authors dwell on the pedagogical aspects of the new course, such as openness, transparency, internal communication, and external deposition of the educational products obtained by participants in the courses. The proposed model of online course is distinguished by a distributed and problem-based character coupled with high level of the transparency and internal openness. Within the framework of the course the participants share Google Documents and Blogs with each other and with the tutor performing peer-to-peer communication. It is shown that proposed model of educator training leads to more effective results than other commonly used MOOCs. After the course is finished, all educational products achieved by participants are archived and become accessible for external users. Their rights are provided by Creative Commons Attribution. As a result of the implementation of the course, the University’s resource of open access educational and didactic materials is being maintained and developed.